Taxonomic and functional shifts in the rumen microbiome of buffalo calves under long-term strategic supplementation of phyto-feed additives - Soni, P.K.; Kala, A.; Agarwal, P.; Deka, Ram Pratim; Rahman, Habibur; Kennady, Vijayalakshmy; Chaudhary, L.C. (Frontiers Media, 2025)
Introduction: The present study aimed to understand the shift in the rumen microbiome of buffaloes fed diets with and without phyto-additives. The rationale was based on the hypothesis that plant-based additives can modulate the microbial population in the rumen, potentially reducing methane production and enhancing fiber degradation. Given the possibility that prolonged use of the same additives may lead to microbial adaptation and diminished efficacy, the study also investigated the effects of periodically switching additives.